Influence of international stakeholder and health-care agendas in the Palestinian Family Survey, 2010: a qualitative assessment of a national health survey. (August 2017) - Ghandour, Rula; Bates, Katie; Imseeh, Sawsan; Mitwalli, Suzan; Nasr, Shiraz; Hammoudeh, Doaa; Coast, Ernestina; Leone, Tiziana; Giacaman, Rita
Abstract: Background: Population health surveys play a vital part in enabling the planning, implementation, and monitoring of national health programmes and policies. However, the construction of these surveys is often determined by international stakeholders' agendas and implementation is restricted by availability of local resources. We used the Palestinian Family Survey (PFS) 2010 as a case study to inform the discussion on health surveys in the Arab region. Methods: We used qualitative research methods involving a detailed document review of all PFS materials (eg, questionnaires, interviewer instructions and training manuals, reports) to assess the construction and implementation of the PFS in the occupied Palestinian territories. We compared the of the PFS 2010 survey instruments with contemporary health policies and practices. Findings: We found a mismatch between the PFS content and data requirements at the national level. Some PFS content appeared to reflect international agendas rather than local health needs–for example, detailed questions about HIV/AIDS in a context with fewer than 100 reported cases since 1988. By contrast, health issues that were important in the context, such as mental health or exposure to violence, were not included in the PFS. There were inconsistencies in data collection by age and sex. For example, women aged 54–59 years were excluded from all survey modules except for the household roster, and there were few questions on the health of women who had never married. Interpretation: Although population surveys are an important source of evidence in resource-poor settings, these findings suggests a need to re-evaluate health surveys, taking into account the necessity of addressing health concerns within their specific national context, while retaining the ability to monitor international health targets. Funding: Emirates Foundation, London School of Economics Middle East Centre.